Impact of severe intellectual disability on proxy instrumental assessment of quality of life. Issue 3 (3rd July 2019) - Bertelli, Marco O.; Bianco, Annamaria; Rossi, Andrea; Mancini, Michele; La Malfa, Giampaolo; Brown, Ivan
ABSTRACT: Background: Proxy quality of life (QoL) evaluation has been reported to be influenced by many factors. The present study was designed to investigate the impact that the presence of severe intellectual disability (ID) may have on proxy attribution of QoL in the instrumental assessment. Methods: The "other person" form (proxy questionnaire) of the Italian adaptation of the Quality of Life Instrument Package (QoL-IP), the BASIQ [BAtteria di Strumenti per l'Indagine della Qualità di Vita] was administered to 20 first-line operators to assess their perceptions of the QoL of 92 subjects with severe ID and 34 volunteers without ID. The 54-item BASIQ measures three psychological domains (Being; Belonging; Becoming) and nine sub-domains, with each item also assessed across four dimensions (Importance; Satisfaction; Decision-making; and Opportunities). Results: Subjects with ID (as rated by proxies) had higher scores on BASIQ domains than those of non-ID subjects except for the sub-domain of Psychological Being. People with ID also received lower scores from proxies on the Decision-making dimension but higher scores on the Opportunities dimension. Differences between groups were statistically significant for most variables. Conclusions: Findings suggest that prejudicial attitudes towards the QoL of people with severe ID may be either absent in proxies or contained within the scope of the excercise. Previous research indicating that non-integrated QoL assessment may give paradoxical results was also supported.